2013
DOI: 10.1371/journal.pone.0079923
|View full text |Cite
|
Sign up to set email alerts
|

Severe Painful Vaso-Occlusive Crises and Mortality in a Contemporary Adult Sickle Cell Anemia Cohort Study

Abstract: BackgroundFrequent painful vaso-occlusive crises (VOCs) were associated with mortality in the Cooperative Study of Sickle Cell Disease (CSSCD) over twenty years ago. Modern therapies for sickle cell anemia (SCA) like hydroxyurea are believed to have improved overall patient survival. The current study sought to determine the relevance of the association between more frequent VOCs and death and its relative impact upon overall mortality compared to other known risk factors in a contemporary adult SCA cohort.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
89
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 31 publications
11
89
0
1
Order By: Relevance
“…In two prospective studies sickle cell patients were selected for HC treatment based on their greater vaso-occlusive severity (Voskaridou et al, 2010;Lobo et al, 2013). Long term follow up showed that these patients survived longer than their non-HC treated counterparts, even though a higher mortality (Platt et al, 1994;Darbari et al, 2013) would have been predicted by their greater vaso-occlusive severity.…”
Section: Discussionmentioning
confidence: 92%
“…In two prospective studies sickle cell patients were selected for HC treatment based on their greater vaso-occlusive severity (Voskaridou et al, 2010;Lobo et al, 2013). Long term follow up showed that these patients survived longer than their non-HC treated counterparts, even though a higher mortality (Platt et al, 1994;Darbari et al, 2013) would have been predicted by their greater vaso-occlusive severity.…”
Section: Discussionmentioning
confidence: 92%
“…Wound healing is a complex, dynamic process that can be simplified in three phases: There are a few treatment principles that guide chronic wound therapy by the practicing sickle cell clinician (Table I): (1) Debride to remove dead tissue and biofilm; (2) open or excise closed wound edges to stimulate proliferation; (3) identify and treat infections; (4) absorb excess exudate to avoid maceration; (5) maintain moist wound surface ("a dry cell is a dead cell"); (6) protect healing wound from infection/trauma; and, most importantly, (7) use some type of compression to avoid venostasis.…”
Section: Principles Of Wound Healing and Wound Care For The Practicinmentioning
confidence: 99%
“…In the 21st century the majority of patients reach adulthood [1][2][3][4] As patients become older, the challenge of end organ damage has risen and among those, chronic ulcers represent a particularly debilitating and poorly understood complication. Their incidence has remained steady despite successful preventative strategies against bacterial infection and stroke [5], and improved supportive care.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The strongest genetic association with chronic kidney disease (CKD) in the general African-American population is homozygosity or compound heterozygosity for two common variants of APOL1, G1 (S342G and I384M substitutions) and G2 (N388 and Y389 deletions), [6][7][8][9][10][11] which is observed in 10-15% of African-Americans. 6,12 Similar to the genetic persistence of the Hb S mutation, which protects against mortality from malaria, the APOL1 G1 and G2 variants are believed to have been selected by affording protection from Trypanosoma brucei rhodesiense infection.…”
Section: Introductionmentioning
confidence: 99%